(untitled) (Fiep Bulletin - online, 2011)
Epidemiology is a science that studies the factors that determine the frequency and distribution of diseases in populations, constituting an indispensable knowledge on the nurse formation. The Academic Monitoring emerges as a way to help professors in their teaching and to integrate the student monitor in entire educational process. With this understanding, this work presents the experiences of an academic nursing in UFRN in monitors in the discipline of Epidemiology and Environmental Health, and aims to promote reflection on monitoring and encouraging ways to strengthen it as an activity that qualifies the academic formation. For this, we used the story of experience, and thus needed from the memory and observations about the experience. The activities were developed by the monitor aiming to attend the objectives proposed in the project of education. Were accomplished participations in planning meetings with the professors, prepared lesson plans and taught under the supervision of the teacher, exchange of experiences with students during classroom and field activities, Essentials activities to the admiration and increasing demand for teaching and incorporating a more qualified role of educator. During this process it was necessary to study and continuous updating of knowledge about the discipline and also a methodological contributions to substantiate the pedagogical act. Through this experience, we could realize its enormous value to the construction of the Professional fututre, since it allowed an awareness of the size of the educational process, the development of skills and teaching skills and knowledge enhancement.